Knowledge Conversion: An Evaluation of BPPT KM Application Utilization as A Knowledge Management System - Ria Ariani; Nur Sanny Rahmawati (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2020)
This paper presents how knowledge being converted through a knowledge management application called BPPT KM App that is managed by Pusat Manajemen Informasi – Badan Pengkajian dan Penerapan Teknologi, and its function used as a knowledge management system. The purpose of this paper is to explain the implementation of knowledge conversion in Badan Pengkajian dan Penerapan Teknologi and to know how the knowledge management system works and the effectiveness of the app. The method used in this paper is qualitative with participative observation approach and narrative review. With these approaches, researchers do the direct investigation of the subject research and involved in the process of knowledge conversion of the app. The result of this study shows that knowledge conversion can be implemented by BPPT employees, whether the employees located in MH Thamrin Jakarta or Puspiptek Serpong, and the SECI indicators have been conducted in the knowledge management system through the app. It can be concluded that BPPT KM App has facilitated knowledge conversion implementation to all BPPT employees remotely and it can be accessed anytime and anywhere, especially in this pandemic situation.